Birth order: An important factor of individual development - Bagdonas, A.; Greblikienė, R.; Kaniavienė, Ž. (Psichologija, 1996)
The relation between birth order on the one side and intelligence and personality features on the other side was investigated. In the 1st study (subjects - 104 students of 8-9 grades of secondary schools from l, 2, and 3-child families) the R. Amthauer’s Intelligence Structure Test was used. The first child has the most favourable conditions for intellectual development (especially in 2-child families). In the 2nd study, (subjects - 240 10-grade students of secondary schools from l, 2, 3, and 4-child families) it was established that the first child in the family shows more internal tendencies than the other children. An external locus of control is a characteristic feature of single children and children from 2-child families. A relation between Myers-Brigg’s psychological types and birth order didn’t occur.